PJMHS 2022
DOI: 10.53350/pjmhs221610247
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Demographic Factors on Oral Health Knowledge and Attitude of patients with Type II Diabetesmellitus Visiting A THQ Hospital in Punjab, Pakistan

Abstract: Aim:Patients suffering from Diabetes Mellitus havea largerpossibilityofdeveloping oral diseases furthermore; those who have uncontrolled and long-duration of Diabetes Mellitusare also at a greater risk for acquiringperiodontaldisorders. The present study intended to investigate the association of oral fitness knowledge and attitude with different demographic factorsin patients with Type II Diabetes Mellitus visiting a secondary care provincial hospitalin Sargodha, Pakistan. Methods: The present study was a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Information regarding oral hygiene maintenance is fundamental in promoting self-prevention as one of the leading causes of gingivitis and periodontitis is plaque. [15][16] It has been reported that flossing in addition to tooth brushing is imperative in controlling the amount of dental plaque. 15 Therefore, the present study was planned to raise awareness regarding the usage of interdental aids in conjunction with tooth brushing among the medical students of district Sheikhupura.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding oral hygiene maintenance is fundamental in promoting self-prevention as one of the leading causes of gingivitis and periodontitis is plaque. [15][16] It has been reported that flossing in addition to tooth brushing is imperative in controlling the amount of dental plaque. 15 Therefore, the present study was planned to raise awareness regarding the usage of interdental aids in conjunction with tooth brushing among the medical students of district Sheikhupura.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated prevalence of diabetes mellitus in Pakistan is 9.8% which is impacted by 10% of males and 9.7% of females. [5][6][7] The worldwide prevalence of diabetic neuropathy is 21.3% -34.5% while the male-female ratio is 1:1.1 which in other words implies that diabetes is further predominant in females (54%) than in males (46%). 8 In patients with Type-II diabetes mellitus due to decreased sensory function of the foot and ankle, a decline in the static and dynamic postural stability performance is noticed.…”
Section: Introductionmentioning
confidence: 99%